2020
DOI: 10.4274/jcrpe.galenos.2019.2019.0142
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Posterior Pituitary, Polydactyly, Midfacial Hypoplasia and Multiple Pituitary Hormone Deficiency due to a Novel Heterozygous IVS11-2A>C(c.1957-2A>C) Mutation in the <i>GLI2</i> Gene

Abstract: A novel heterozygous IVS11-2A>C(c.1957-2A>C) mutation in the GLI2 gene is reported. There was an extremely distinct phenotypical expression in two siblings and their father. The index case was a boy who developed cholestasis and hypoglycaemia in the neonatal period. He had bilateral postaxial polydactyly, mid-facial hypoplasia, high palatal arch, micropenis, and bilateral cryptorchidism. Laboratory examination revealed a diagnosis of multiple pituitary hormone deficiency. There was sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Some of the most commonly reported characteristics, including anterior pituitary lobe hypoplasia, ectopic posterior pituitary lobe identified on MRI, the resulting pituitary deficiencies, postaxial polydactyly, and facial dysmorphisms, most commonly cleft lip and palate, were given their own column in order to facilitate comparing and contrasting the different families' characteristics. True holoprosencephaly was only identified in 2/37 patients and was the rarest characteristic identified on this review, although not all patients had imaging since it was obtained when clinically indicated in most cases Table 2 4‐7,10 . Over half (20/37) of the GLI2 gene mutation patients in this study were identified to have polydactyly, making it the most common characteristic 4‐7,10 …”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…Some of the most commonly reported characteristics, including anterior pituitary lobe hypoplasia, ectopic posterior pituitary lobe identified on MRI, the resulting pituitary deficiencies, postaxial polydactyly, and facial dysmorphisms, most commonly cleft lip and palate, were given their own column in order to facilitate comparing and contrasting the different families' characteristics. True holoprosencephaly was only identified in 2/37 patients and was the rarest characteristic identified on this review, although not all patients had imaging since it was obtained when clinically indicated in most cases Table 2 4‐7,10 . Over half (20/37) of the GLI2 gene mutation patients in this study were identified to have polydactyly, making it the most common characteristic 4‐7,10 …”
Section: Discussionmentioning
confidence: 74%
“…True holoprosencephaly was only identified in 2/37 patients and was the rarest characteristic identified on this review, although not all patients had imaging since it was obtained when clinically indicated in most cases Table 2 4‐7,10 . Over half (20/37) of the GLI2 gene mutation patients in this study were identified to have polydactyly, making it the most common characteristic 4‐7,10 …”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations